2020
DOI: 10.1002/cpt.2091
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of LAG‐3+ T Cells Translated to Pharmacology and Improvement in Psoriasis Disease Activity: A Phase I Randomized Study of mAb GSK2831781

Abstract: Activated T cells drive a range of immune-mediated inflammatory diseases. LAG-3 is transiently expressed on recently activated CD4 + and CD8 + T cells. We describe the engineering and first-inhuman clinical study (NCT02195349) of GSK2831781 (an afucosylated humanized IgG1 monoclonal antibody enhanced with high affinity for Fc receptors and LAG-3 and antibody-dependent cellular cytotoxicity capabilities), which depletes LAG-3 expressing cells. GSK2831781 was tested in a phase I/Ib, double-blind, placebo-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 45 publications
4
44
1
Order By: Relevance
“…Preliminary results showed that GSK2831781 is pharmacologically active with a tolerable safety profile, and provides early evidence of improvement in psoriasis. 59 GSK2831781 treatment reduced pro-inflammatory gene expression (IL-17A, IL-17F, IFNg, and S100A12), and upregulated genes associated with skin barrier functions (CDHR1). TSR-033.…”
Section: Anti-lag-3 Monoclonal Antibodiesmentioning
confidence: 99%
“…Preliminary results showed that GSK2831781 is pharmacologically active with a tolerable safety profile, and provides early evidence of improvement in psoriasis. 59 GSK2831781 treatment reduced pro-inflammatory gene expression (IL-17A, IL-17F, IFNg, and S100A12), and upregulated genes associated with skin barrier functions (CDHR1). TSR-033.…”
Section: Anti-lag-3 Monoclonal Antibodiesmentioning
confidence: 99%
“…GSK2831781 , derived from IMP731 Immunetep’s antibody, developed in monotherapy by GlaxoSmithKline in 3 clinical trials (2 phase I and 1 phase II) for psoriasis and ulcerative colitis. The ulcerative colitis phase II trial was terminated after an interim analysis [ 83 ], but phase I results show good tolerability, safety and inflammation regulation profiles [ 84 ].…”
Section: Preclinical and Clinical Development Of Opdualagmentioning
confidence: 99%
“…Moreover, a cytotoxic LAG-3 Ab has been evaluated in a nonhuman primate model of delayed-type hypersensitivity ( 109 ). Contrarily, in a phase I clinical trial investigating psoriasis the depletion of LAG-3–positive T cells was linked to a reduced Th1-driven skin inflammation, lasting even in the absence of the depleting antibody ( 110 ).…”
Section: Lag-3mentioning
confidence: 99%